Political Identity Ownership: Symbolic Contests to Represent Members of the Public. (June 2020) - Kreiss, Daniel; Lawrence, Regina G; McGregor, Shannon C
This study develops the concept of identity ownership to explain how, in the course of electioneering, candidates perform their own identities to align with groups whose support they seek. We frame this from a communication perspective—media are increasingly central sites for constructing and conveying the identity of candidates and the groups of constituents they seek to represent. In developing this model, we seek to bring this identity-based framework more to the fore in communication research, as well as place communication at the center of studies of social identity. We argue that seeing political identities as dynamic and actively performed provides an opportunity to analyze communications based not only on their informational value but also on their identity value.